Nomophobia: Dampak Perkembangan Teknologi Di Era Modern - Dinar Ayu Chandra Agustin; Khilda Luqyana Arifin (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah IAI Uluwiyah Mojokerto, 2022)
In modern times, the use of smartphones is not limited by circles, ranging from children, teenagers, to parents, using them both to communicate, get information and build social networks. Social networking itself is increasingly popular among modern society. Social network addiction is a person's compulsive behavior towards the use of internet-based social networks, which can be connected from individual to individual and even in groups without meeting face to face. Social networks are also at the root of many people's addiction to smartphones. Nomophobia is an abnormal feeling of anxiety caused by being away from a smartphone. Nomophobia is the result of the times, the sophistication of technology and the information it contains encourages someone to create many new things, including smartphones with many functions. Advances in science and technology bring many advantages to our lives, so use them wisely. It is hoped that guidance and counseling services to overcome nomophobia can be developed effectively and efficiently. Modern society is in dire need of guidance and counseling services to reduce the level of addiction to cell phones.